Perspektif Hukum Ekonomi Syariah Dalam Jual Beli Dengan Metode Cash On Delivery (COD) Di E-Commerce Shopee - Abdillah, Syaik; Melindah, Devi (STAI Al Musaddadiyah Garut, 2022)
Shopee e-commerce is an online-based shopping application that is widely used by people in the era of all-digital development. The payment method that is most in demand by Shopee e-commerce users is the cash on delivery (COD) method, because it has an uncomplicated payment method and also has various advantages. However, in its implementation, there are several obstacles where these problems are considered to be detrimental to the buyer. The formulation of the problem in this study is: How is the implementation of buying and selling with the cash on delivery (COD) method in Shopee e-commerce? What is the perspective of sharia economic law in buying and selling with the cash on delivery (COD) method in Shopee e-commerce? From the formulation of the problem, the target of this study is 1. To find out the implementation of buying and selling with the cash on delivery (COD) method on Shopee e-commerce. 2. To find out the perspective of sharia economic law in buying and selling with the cash on delivery (COD) method at Shopee e-commerce. This research is included in the type of library research using descriptive, analytical and comparative methods with a qualitative approach. Based on the results of the study, it can be concluded that the implementation of buying and selling with the cash on delivery (COD) method in Shopee e-commerce has fulfilled the pillars and conditions in buying and selling so that buying and selling like this is permissible and halal and includes popular buying and selling. Keywords: Sharia Economy, Buying and Selling, Cash on Delivery (COD), E-commerce